2006
DOI: 10.1055/s-2006-923849
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ventilatory Thresholds from Heart Rate Variability in Well-Trained Subjects during Cycling

Abstract: The purpose of this study was to implement a new method for assessing the ventilatory thresholds from heart rate variability (HRV) analysis. ECG, VO2, VCO2, and VE were collected from eleven well-trained subjects during an incremental exhaustive test performed on a cycle ergometer. The "Short-Term Fourier Transform" analysis was applied to RR time series to compute the high frequency HRV energy (HF, frequency range: 0.15 - 2 Hz) and HF frequency peak (fHF) vs. power stages. For all subjects, visual examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
164
1
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(191 citation statements)
references
References 36 publications
14
164
1
12
Order By: Relevance
“…X-axis = time (s), Y-axis = frequency (Hz), Z-axis = power spectral density (PSD, ms 2 /Hz) (Cottin et al 2006). …”
Section: Time-frequency Analysismentioning
confidence: 99%
“…X-axis = time (s), Y-axis = frequency (Hz), Z-axis = power spectral density (PSD, ms 2 /Hz) (Cottin et al 2006). …”
Section: Time-frequency Analysismentioning
confidence: 99%
“…second lactate and ventilatory threshold -LT 2 and VT 2 , respectively) (3,5). As a result, studies have suggested that HRV analysis may be a potential and useful tool to estimate the exercise intensity of the first and second physiological thresholds (4,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Este achado corrobora a relação entre o limiar determinado pela VFC e a resposta metabólica de condição estável da concentração sanguínea de lactato. No entanto, embora outros estudos tenham indicado a possível relação entre a resposta da VFC e o LV 1 (ALONSO et al, 1998;ANOSOV et al, 2000;COTTIN et al, 2006;TULPPO et al, 1996) e o primeiro limiar de lactato (LIMA; KISS, 1999), o presente estudo indica uma possibilidade de proximidade do LVFC, como determinado por Lima e Kiss (1999), com o segundo limiar, uma vez que a carga constante correspondente ao LVFC conduziu a valores de lactato próximos e acima de 4 mmol.l -1 para 50% dos sujeitos, e não próximos a 2 mmol.l -1 , como seria a expectativa para o primeiro limiar (RIBEIRO, 1995). Valores em torno de 4 a 6 mmol.l -1 têm sido observados na carga de máximo estado estável de lactato em exercícios realizados em ciclos ergométricos por sujeitos treinados e que praticam atividade física de maneira recreacional (BENEKE;HUTLER;LEITHAUSER, 2000;BENEKE et al, 2003;FIGUEIRA et al, 2007), reforçando a hipótese de que nossos achados indicam uma possível relação da carga deste limiar da VFC com a maior carga em condição de estabilidade do lactato.…”
Section: Ab -Lvfc Lvfc Ac -Lvfcunclassified
“…Em seguida, outros estudos verificaram a relação entre limiares da VFC determinados por diferentes métodos e o LV 1 , identificando similaridades entre os valores e/ou correlação significativa entre estas variáveis (ANOSOV et al, 2000;COTTIN et al, 2006). Cottin et al (2006) demonstraram que também o segundo limiar ventilatório (LV 2 ) poderia ser determinado a partir da análise da VFC no domínio da freqüência.…”
Section: Introductionunclassified
See 1 more Smart Citation